"موسوعۃ التاریخ الاسلامی والحضارۃ الاسلامیہ"میں احادیث صحیح بخاری سے متعلق ڈاکٹراحمد شلبی کے مؤقف کا تحقیقی وتخریجی جائزہ: Encyclopedia of Islamic History and Islamic Civilization” Research and Ecclesiastical Study of Dr. Ahmad Shalabi’s Position on Hadith of Sahih Bukhari - Kaukab, Dr.Tasmia; Nosheen, Sobia; Naimat Ullah, Muhammad (Al-Amīr Research Journal for Islamic Studies, 2023)
Dr. Ahmed Jabullah Shalabi is one of the famous teachers in Egypt. One of his multitudinous is “موسوعة التاریخ الاسلامی والحضارةالاسلامية"Encyclopedia of Islamic History and Islamic Civilization". In a way, it is an encyclopedia of Islamic history. And since Dr. Ahmad Shalabi is one of the modernist scholars and mujtahids, the way in which he has described Islamic history in the said book needs to be weighed in the correct scale. In this ten-volume book, the researcher has tried to research only the hadiths of Sahih Bukhari, narrated in the first volume of Mousooah. This is the age of materialism and modernism. In this Western invading environment, people are moving away from religion. The reason of this distance is lack of religious knowledge and facts. Therefore, due to lack of knowledge, such people are quickly accepting the influence of the ideas of the scholars who are intimidated by modernists, Orientalists and disbelievers and follow these theories without any research.There is a need to weigh these innovative ideologies in the correct Shariah scale of Islam and present them to the people so that there is a distinction between right and wrong. The subject under discussion is a research and extravagant review of the views, opinions and ideas of Dr. Ahmed Shalabi about the hadiths of Sahih Bukhari.The descriptive research method is used for this as far as possible, and basic sources are sufficient for the expression of an idea or opinion. Arabic, English and Urdu books are used equally. Basic books on history, biography, hadith and principles of hadith are used. Key words: Ahmad shalbi, Sahih Bukhari, Mousoa tul tarikh al-islami, Hadith.